(untitled) (Educação e Pesquisa, 2003)
This article analyzes the discourse of current teacher education policies in Brazil, synthesizing the results of the study entitled Information and communication technologies and distance learning: the discourse of the Ministry of Education. The text is organized in four sections. The first section deals with the meanings attached to technologies in education, in their relation to the ways in which information and communication technologies (ICTs) have been incorporated into education processes. To that end, the text focuses on the defining perspectives and proposals of the recontextualization of the ICTs found in the pedagogical discourse. The second section discusses the set of changes in meaning that have been giving support to teacher education policies, with special emphasis on notions such as that of the ''digital watershed'', as well as on the relations among the shift of teaching towards activity and task, the teaching education proposal based on competencies, and the intensive use of technologies. In other words, this section is centered on the relation between the ICTs and distance learning, considered in its multiple dimensions. The third section brings out the reductions operated along the process of incorporating technologies in education as revealed by the Discourse Analysis of MEC texts, whose main drive has been that of prioritizing teachers distance learning consonant with the recommendations made by international bodies to developing countries. Finally, the fourth section refers to the current trends in teacher education policies, resuming the discussion and pointing to the issues related to the meanings of technologies and to the modes of their assimilation in different educational contexts.